Knowledge-Worker Productivity in Defense Industry: The Role of Knowledge Management through Employees’ Adaptability and Job Satisfaction - Wardhani, Nawangsari; Noermijati, Noermijati; Sunaryo, Sunaryo (Media Ekonomi dan Manajemen, 2022)
This research aims to investigate the direct effect of knowledge management on knowledge-worker productivity and the indirect effect mediated by employees' adaptability and job satisfaction. The research was conducted at PT. Pindad (Persero) Malang as a specific knowledge-based manufacturing industry company. The research population is employees who work in the department that is closely related to the knowledge of ammunition products. Furthermore, 203 employees became the research sample taken proportionally and randomly from the population using proportionate random sampling technique. The data analysis method was carried out using a structural equation modeling (SEM) model with a partial least square (PLS) approach. The results indicate that knowledge management has no significant effect on knowledge-worker productivity, but knowledge management has a significant effect on adaptability, and adaptability has a significant effect on knowledge-worker productivity. Knowledge management also has a significant effect on job satisfaction, and job satisfaction also has a significant effect on knowledge-worker productivity. Thus, adaptability and job satisfaction have a full mediating role on the effect of knowledge management on knowledge-worker productivity. This research contributes fill the research gap on the influence of knowledge management on knowledge-worker productivity with the presence of adaptability and job satisfaction as a mediating variable.